2003
DOI: 10.1097/01.ccm.0000095463.72353.ad
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines for the maintenance of patient physical safety in the intensive care unit: Use of restraining therapies—American College of Critical Care Medicine Task Force 2001–2002

Abstract: The task force developed nine recommendations with regard to the use of physical restraints and pharmacologic therapies to maintain patient safety in the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
128
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 42 publications
1
128
1
6
Order By: Relevance
“…These findings contrast with the guidelines of the Society of Critical Care Medicine on the use of restraining therapies, in which chemical restraint (or sedation) is mentioned as an alternative to physical restraint. 1,12 However, the guidelines were published in 2003, and since www.ajcconline.org then several investigators 24,25 have reported harmful effects of sedation. We think that chemical restraint should be used with caution, and in accordance with current sedation guidelines.…”
Section: Multivariate Univariatementioning
confidence: 99%
See 3 more Smart Citations
“…These findings contrast with the guidelines of the Society of Critical Care Medicine on the use of restraining therapies, in which chemical restraint (or sedation) is mentioned as an alternative to physical restraint. 1,12 However, the guidelines were published in 2003, and since www.ajcconline.org then several investigators 24,25 have reported harmful effects of sedation. We think that chemical restraint should be used with caution, and in accordance with current sedation guidelines.…”
Section: Multivariate Univariatementioning
confidence: 99%
“…Participation of a patient's visiting relatives in the healing process may help the patient and the relatives regain some control over the situation, and therefore reduce the use of physical restraint. 1 Use of "boxing gloves" and use of "splints" are different restraining methods that allow patients to move their limbs but prevent refined motor functions such as grasping a tube or catheter. Finally, securing catheters and endotracheal tubes may decrease the concern that a patient would remove these devices and thus reduce the use of physical restraint.…”
Section: Multivariate Univariatementioning
confidence: 99%
See 2 more Smart Citations
“…Canada and British Columbia have legislations (Currie, 1997). While the UK, however, does not accept physical restraint use at all, it is common in the US, Australia, and Europe (Maccioli et al, 2003;Royal College of Nursing, 2004;Van Norman & Palmer, 2001). Nurses and scientists from other disciplines tried to agree on physical restraint use starting in 1988 no consensus reached yet on its use in hospitals (Bower & McCullough, 2000).…”
Section: Department Of Health and Humanmentioning
confidence: 99%